Influence of Hospital Readiness in Handling Covid-19 on Covid-19 Incidents - Solichah, Siti; Husein, Rahmawati; Rosa, Elsye Maria (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effect of hospital readiness in handling COVID-19 on the incidence of COVID-19 at Aisyiyah Siti Fatimah Hospital, Tulangan Sidoarjo, to optimize the ability to deal with the COVID-19 disaster. This type of research is a quantitative study with a cross-sectional analytic observational design. The results showed that most of the employees of Aisyiyah Fatimah Hospital in Tulangan Sidoarjo were aged between 21-30 years, namely 109 people (61.2%). Based on gender, most of the respondents were women, namely 156 people (87.6%). Based on education, most of the respondents have D3 education as many as 81 people (45.5%). Meanwhile, based on years of service, most respondents worked for 1 – 5 years as many as 87 people (48.9%). Bivariate analysis showed that staff had a positive and significant effect on the number of suspected Covid-19 patients. In conclusion, the team is the more dominant factor or variable in influencing the handling of Covid-19 in the Covid-19 incident at Aisyiyah Siti Fatimah Hospital, Tulangan Sidoarjo. Keywords: Covid-19 Incidence, Hospital Readiness, Handling Covid-19